History of the Naukan Yupik Eskimo dictionary with implications for a future Siberian Yupik dictionary - Jacobson, Steven (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2005)
AbstractNaukan is a Yupik Eskimo language spoken now by only a few people on the Russian side of the Bering Strait, but with strong Alaskan affinities. Naukan speaker Dobrieva of Lavrentiya, linguist Golovko of St. Petersburg, and linguists Jacobson and Krauss of Fairbanks have compiled a Naukan dictionary in two parallel volumes: Naukan in a latin-letter orthography to English, and Naukan in the modified Cyrillic alphabet used for Chukotkan Eskimo languages to Russian. It was both appropriate and beneficial that this project involved people from Alaska, European Russia, and Chukotka. The dictionary was recently published by the Alaska Native Language Center of the University of Alaska Fairbanks. The Naukan dictionary in two parallel volumes can serve as a model for a new dictionary of (Central) Siberian Yupik, a language spoken, at least ancestrally, by roughly equal numbers on St. Lawrence Island Alaska and in the New Chaplino-Sirenik area of Chukotka, Russia. Such a dictionary could help to reinvigorate that language and allow it better to serve as a bridge between the two halves of a single people and culture divided only in recent decades by a boundary not of their own making.